2014
DOI: 10.1371/journal.pone.0112555
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biophysical Characterization of Bacillus thuringiensis Insecticidal Proteins Cry34Ab1 and Cry35Ab1

Abstract: Bacillus thuringiensis strains are well known for the production of insecticidal proteins upon sporulation and these proteins are deposited in parasporal crystalline inclusions. The majority of these insect-specific toxins exhibit three domains in the mature toxin sequence. However, other Cry toxins are structurally and evolutionarily unrelated to this three-domain family and little is known of their three dimensional structures, limiting our understanding of their mechanisms of action and our ability to engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 59 publications
0
69
0
1
Order By: Relevance
“…72 While most of the CCS values have been for tryptic peptides, there is recent and significant efforts being made in the quantitative IM analysis of structurally-interesting peptide and protein classes, including helical peptides, 174176 metalloproteins, 177180 intrinsically-disordered proteins, 181184 metamorphic proteins, 185,186 amyloids, 187194 and membrane-bound proteins and assemblies. 117,195198 The last three years has seen a balance of cross section reporting across most of the chemical classes, including lipids and carbohydrates. The exception is nucleotide CCS values, which, aside for the 2009 study from McLean and coworkers, 68 have been published in small numbers spread across several studies and years, and currently comprise about 1% all CCS values reported.…”
Section: Ccs Coverage Over Timementioning
confidence: 99%
“…72 While most of the CCS values have been for tryptic peptides, there is recent and significant efforts being made in the quantitative IM analysis of structurally-interesting peptide and protein classes, including helical peptides, 174176 metalloproteins, 177180 intrinsically-disordered proteins, 181184 metamorphic proteins, 185,186 amyloids, 187194 and membrane-bound proteins and assemblies. 117,195198 The last three years has seen a balance of cross section reporting across most of the chemical classes, including lipids and carbohydrates. The exception is nucleotide CCS values, which, aside for the 2009 study from McLean and coworkers, 68 have been published in small numbers spread across several studies and years, and currently comprise about 1% all CCS values reported.…”
Section: Ccs Coverage Over Timementioning
confidence: 99%
“…All of the other Toxin_10 proteins act with their specific partner proteins to form binary toxins as follows: BinA and BinB (both Toxin_10 proteins) (Broadwell et al, 1990;Oei et al, 1990); Cry34 (aegerolysin-like) and Cry35 (Toxin_10) (Kelker et al, 2014;Masson et al, 2004); Cry48 (3-domain) and Cry49 (Jones et al, 2007). The role of each protein in these binary pairs is clearly significant to understanding the specificity of the toxins and potential binding of both components presents further challenges to prediction.…”
Section: Sphaericus B Thuringiensis Bacillus Cereus and Paenibamentioning
confidence: 99%
“…Cry21 The structures of the insecticidal toxins BinB (PDB 3WA1 (Srisucharitpanit et al, 2014)), Cry35 (PDB 4JP0 (Kelker et al, 2014)), Cry23 (PDB 4RHZ), Cry45 (PDB 2D42 (Akiba et al, 2006)), Cry46 (PDB 2ZTB (Akiba et al, 2009)) and Cry51 (PDB 4PKM (Xu et al, 2015)) are…”
Section: Cry1mentioning
confidence: 99%
See 2 more Smart Citations